American Academy of Neurology Telehealth Position Statement. (17th August 2021) - Hatcher-Martin, Jaime M.; Busis, Neil A.; Cohen, Bruce H.; Wolf, Rebecca A.; Jones, Elaine C.; Anderson, Eric R.; Fritz, Joseph V.; Shook, Steven J.; Bove, Riley M.
Abstract : Telehealth services complement in-person neurologic care. The American Academy of Neurology supports patient access to telehealth services regardless of location, coverage for telehealth services by all subscriber benefits and insurance, equitable provider reimbursement, simplified state licensing requirements easing access to virtual care, and expanding telehealth research and quality initiatives. The roles and responsibilities of providers should be clearly delineated in telehealth service models.